Device closure of 'complex' postinfarction ventricular septal defect. (January 2015) - Capasso, Fabio; Caruso, Aurelio; Valva, Giuseppe; Lonobile, Tommaso; Grimaldi, Maria G.; Santoro, Giuseppe
Abstract : Ventricular septal defect (VSD) is a life-threatening complication of acute myocardial infarction (MI), resulting in high mortality rate even in the case of a timely approach by surgical repair. Transcatheter closure is nowadays a reliable alternative to surgery, although currently deemed challenging or unsuitable in large and complex VSD. This article reports on a successful transcatheter approach in a critically ill patient with subacute right coronary-related, complex postinfarction VSD. In this patient, two sequentially deployed Amplatzer Septal Occluder devices stabilized the clinical conditions and hemodynamic parameters.